2016
DOI: 10.1017/cjn.2016.311
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of Tuberous Sclerosis Complex: The Experience of a Provincial Clinic

Abstract: This study outlines the multisystem manifestations of TSC, observed through a large pediatric referral center. Epilepsy and neuropsychiatric disorders are the major source of morbidity in this age group and provide many challenges to the treating clinician. Because a subset of the study population is still quite young, the prevalence of neuropsychiatric disorders is likely underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 53 publications
(84 reference statements)
0
32
1
Order By: Relevance
“…In our study, 9 (56.2%) out of 16 patients presented with convulsions. The prevalence of seizure as one of the initial TSC manifestations was lower than those recently reported from the studies published by Almoberak et al, [10] Wilbur et al, [4] Sing Au et al, [7] and İncecik et al [8] at 68.2%, 91%, 74.8%, and 89.1%, respectively. Similar results were found in the studies by Saltuk et al [11] at 42.8% and Rubilar et al [12] at 48.7%.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In our study, 9 (56.2%) out of 16 patients presented with convulsions. The prevalence of seizure as one of the initial TSC manifestations was lower than those recently reported from the studies published by Almoberak et al, [10] Wilbur et al, [4] Sing Au et al, [7] and İncecik et al [8] at 68.2%, 91%, 74.8%, and 89.1%, respectively. Similar results were found in the studies by Saltuk et al [11] at 42.8% and Rubilar et al [12] at 48.7%.…”
Section: Discussioncontrasting
confidence: 55%
“…In our study, 2 (12.5%) patients had these patches. Rubilar et al, [12] Wilbur et al, [4] and Sing Au et al [7] found the frequency of adenoma sebaceum to be 47.6%, 43%, and 60.1%, respectively. Since the number of cases in our study is low, we think that the frequency of adenoma sebaceum is lower than that in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the Quality in Prognosis Strategy (QUIPS) tool, the most commonly found risk factors for bias in the studies reviewed included study participation, ASD measure, and study confounders. Many [14] of the reviewed articles included participants drawn from one clinic or hospital (18,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32); others [5] had a specific age range (12,13,(33)(34)(35) or a particular subset of the TSC population (18, 35-47, 49, 50). Only 18 of the included articles reported the diagnostic criteria for ASD ( Table 1).…”
Section: Search Strategy and Article Selectionmentioning
confidence: 99%
“…Deficits across all domains of the Bayley Scales of Infant Development (BSDI) at 1 year of age were predictive of higher autism traits on the Autism Diagnostic Observation Schedule (ADOS) at 2 years within a prospective study of infants with TSC (n = 82) in 10 sites across Europe and Australia (34). ID is often more common in TSC patients with ASD than those with TSC alone (31). Behavioral problems have been reported to be exacerbated by seizure frequency and a mixed seizure profile (24).…”
Section: Phenotype/behaviormentioning
confidence: 99%